L.-J. Lebret: a human development ethics grounded in empirical social research and a global perspective. Issue 2 (4th May 2021) - Gasper, Des
ABSTRACT : Three themes in the work of Louis-Joseph Lebret (1897–1966) have especial relevance for current development ethics: first, the importance of counterbalancing a disciplinary philosophical or theological orientation with strong bases in empirical life-experience, practical learning and social sciences; second, the necessity to study capitalism not only 'development', and concrete life-needs not only a generalised notion of 'freedom'; and third, the imperative to employ global and cosmopolitan frames besides national and 'community' ones. These themes came to distinguish Lebret as a development ethicist. He began with the first and second from the 1930s, under his banner of 'Économie et Humanisme'. The third emerged later in consequence of his studies across an interconnected world. The paper elucidates and discusses the three themes in turn. The subsequent sections then briefly consider Lebret's legacies, influence and continuing relevance: directly, within the Catholic Church's perspectives since the 1960s on human and global development; and indirectly, for secular work on 'human development' and in Anglophone development ethics.